Dampak Penyaluran Zakat Produktif Dalam Bentuk Beasiswa Terhadap Mustahik Pada Lembaga Rumah Zakat - Ayi Suryana; Fenny Damayanti Rusmana; Opan Arifudin (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research is motivated by the fact that to improve the quality of education, one of the efforts that can be taken is by optimizing productive zakat in the form of scholarships. The aim of this research is to determine the effect of productive zakat distribution in the form of scholarships on mustahik. This type of research is qualitative research using primary data. The method used is descriptive qualitative to formulate and interpret data. The research results show that productive zakat in the form of scholarships influences mustahik, which means that the distribution of productive zakat is right on target. Giving zakat to mustahik in the management of productive zakat as capital, namely, to carry out independent economic activities in the form of a business, namely, to develop or increase the economic level and status as well as the productivity potential of mustahik and improve the welfare of mustahik.